Virulence of Syrian Entomopathogenic Nematode Isolates Against of Galleria mellonella (Lepidoptera: Pyralidae) - أحمد , محمد; ألوف , ندى; علي, مي (Latakia University Journal -Biological Sciences Series, 2022)
The virulence of three native isolates of Entomopathogenic Nematodes (EPNs) Heterorhabditis 160, Heterorhabditis 136, Steinernema 22, was evaluated using the last instar of Galleria mellonella as host. Four bioassays were conducted to compare them. (i) Exposure time assay, the isolate H.136 recorded the highest mortality rate within 15 minutes. Less significant differences in mortality rates among isolates were observed by increasing the exposure time intervals. (ii) Dose-response assay, all the studied isolates showed 100% mortality rate at the dose of 40 infective juveniles (IJ) per insect larva. H.136 caused highest mortality rate (41.66%), at the dose of 5 IJ/L. Where the isolate S. 22 revealed the lowest mortality rate (20.33%). (iii) One-On-One assay, the mortality rates among all isolates presented close results, where the isolate H.136 was the highest. (iv) Sand column assay, the results showed that the ability of isolates to find, penetrate and kill the host, with significant difference between them. Propit analysis was conducted to calculate the lethal half-time (LT50) and lethal half-dose (LD50). The findings presented that the most virulence isolate H.136 leaded 22 minutes as LT50 and 5.42 infective juveniles per larva as LD50.